4-Thiazolidinone derivatives as potent antimicrobial agents: microwave-assisted synthesis, biological evaluation and docking studies. Issue 2 (19th November 2014) - Pitta, Eleni; Tsolaki, Evangelia; Geronikaki, Athina; Petrović, Jovana; Glamočlija, Jasmina; Soković, Marina; Crespan, Emmanuele; Maga, Giovanni; Bhunia, Shome S.; Saxena, Anil K.
Abstract : A series of ten thiazolidin-4-one derivatives was synthesized and evaluated for their antibacterial, antifungal and HIV-1 reverse transcriptase (RT) inhibitory activity. Abstract : As a part of our ongoing research in the development of new antimicrobials, herein, we report the synthesis of ten compounds which combine three bioactive moieties: thiazole, adamantane and 4-thiazolidinone. Evaluation of their antibacterial activity revealed that the newly synthesized compounds exhibited remarkable growth inhibition of a wide spectrum of Gram-positive bacteria, Gram-negative bacteria and fungi. The majority of the compounds displayed greater antibacterial activity than the reference drugs (ampicillin and streptomycin), while the antifungal activity was significantly higher than that of the reference drugs bifonazole and ketoconazole. Additionally, the title compounds were screened for HIV-1 reverse transcriptase inhibitory activity, showing no significant activity. Moreover, docking studies were performed in order to explore possible binding modes at the MurB protein of S. aureus.